Konvergensi Media Tribun Jatim : Strategi Transformasi Konten Dan Ekspansi Audiens - Arya Pratama; Julyanto Ekantoro; Tira Fitriawardhani (UNIVED PRESS, Universitas Dehasen Bengkulu, 2026)
The era of digital disruption has triggered a drastic shift in public media consumption behavior, characterized by a significant decline in print media circulation nationwide. To respond to this phenomenon, conventional media companies are compelled to undertake strategic adaptation measures to maintain their relevance. This study aims to explore and analyze the implementation of media convergence at Tribun Jatim, focusing deeply on three primary dimensions: organizational restructuring of the editorial department, transformation of news content formats, and the mechanization of multiplatform distribution patterns. A qualitative descriptive approach was applied in this study through participatory observation, in-depth interviews with the online editorial management and social media teams of Tribun Jatim, and literature review analysis. The research findings reveal that Tribun Jatim has integrated the convergence process comprehensively. At the organizational management level, newsroom restructuring has taken place, giving rise to specific new roles such as Social Media Specialist, Creative Content, and Multimedia Journalism, alongside the implementation of a real-time and dynamic coordination system. In terms of content operations, conventional text-and-photo-based news is transformed into various multimedia (audio-visual) formats adaptive to the unique characteristics of each digital platform, including Instagram, YouTube, Facebook, Twitter/X, and the web portal. The strategy for expanding audience segmentation is optimized through the utilization of actual analytical data (reach, engagement rate, shares) to map demographic preferences and target the long tail audience, specifically Gen Z and Millennials. Theoretically, this process reflects the models of convergence culture and mediamorphosis, which effectively preserve the existence and value of local journalism while expanding reader reach in the digital age